Students’ Motivation for Learning Mathematics during the Covid-19 Pandemic - Aryani, Ni Made Rukni; Suarjana, I Made (International Journal of Elementary Education, 2022)
Many students have less motivation to learn in the learning process. Thus, made students have difficulties in learning. This study aimed to analyze the factors of low student motivation in learn mathematics. This research used descriptive qualitative research. The subjects in this study were 5th-grade students, as many as 16 people. Data collection methods used were questionnaires, observations, and interviews. Instruments of data collection using questionnaires and observation sheets. The data analysis method was carried out descriptively, which was presented in brief descriptions, percentages, diagrams, and physical evidence. The results showed that the average score of learning motivation was 58.06 and was in the average interval. Thus, it is known that the learning motivation of 5th-grade students is still relatively low, which is influenced by internal and external factors of students. The solution that can be done to increase students' learning motivation is to create a pleasant learning atmosphere for students. This research can provide teachers with an understanding of making improvements in the learning process to improve students' learning achievement in mathematics.